Healthy adults supplemented with a nutraceutical formulation containing Aloe vera gel, rosemary and Poria cocos enhances the effect of influenza vaccination in a randomized, triple-blind, placebo-controlled trial - Lewis, Erin D.; Crowley, David C.; Guthrie, Najla; Evans, Malkanthi (Frontiers in Nutrition, 2023)
The study objective was to examine the role of a formulation, UP360, containing rosemary and Poria cocos extracts and Aloe vera gel powder, in healthy adults on supporting immune function with influenza vaccination. A 56-day randomized, triple-blind, placebo-controlled, parallel study consisted of a 28-day pre-vaccination period, an influenza vaccination on Day 28 and a 28-day post-vaccination period. Men and women ages 40-80 who had not yet been vaccinated for the flu were randomized to UP360 or Placebo (n=25/group). At baseline, Days 28 and 56, blood lymphocyte populations, immunoglobulins (Ig) and cytokines were measured, and quality of life (QoL) questionnaires administered. The Wisconsin Upper Respiratory Symptom Survey (WURSS)-24 was completed daily by participants to measure incidence of upper respiratory tract infection (URTIs). In the post-vaccination period, TCR gamma-delta (γδ+) cells, known as γδ T cells, increased with UP360 supplementation compared to Placebo (p<0.001). The UP360 group had a 15.6% increase in influenza B-specific IgG levels in the post-vaccination period (p=0.0006). UP360 significantly increased the amount of circulating glutathione peroxidase (GSH-Px) from baseline at Day 28 (p=0.0214), an enzyme that is important for neutralizing free radicals. While UP360 supplementation initially decreased levels of anti-inflammatory cytokine IL-1RA in the pre-vaccination period, IL-1RA levels were increased in the post-vaccination period (p≤0.0482). Levels of IL-7 increased from baseline at Day 56 with UP360 supplementation (p=0.0458). Despite these changes in immune markers, there were no differences in URTI symptoms or QoL between UP360 and Placebo. These results suggest UP360 supplementation was beneficial in eliciting a healthy, robust immune response in the context of vaccination. No changes in subjective measures of URTI illness or QoL demonstrated that participants’ QoL was not negatively impacted by UP360 supplementation. There were no differences in clinical chemistry, vitals or adverse events confirming the good safety profile of UP360. The trial was registered on the International Clinical Trials Registry Platform (ISRCTN15838713).